Vortex input files for PVA on Southern Resident Killer Whales ... - Lacy, Robert C (Zenodo, 2023)
Input files for publication: Lacy, R.C., R. Williams, E. Ashe, K.C. Balcomb III, L.J.N. Brent, C.W. Clark, D.P. Croft, D.A. Giles, M. MacDuffee, and P.C. Paquet. 2017. Evaluating anthropogenic threats to endangered killer whales to inform effective recovery plans. Scientific Reports 7:14119. doi: 10.1038/s41598-017-14471-0. ...